-5/2u+1/3=-7/4u-3

Simple and best practice solution for -5/2u+1/3=-7/4u-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5/2u+1/3=-7/4u-3 equation:



-5/2u+1/3=-7/4u-3
We move all terms to the left:
-5/2u+1/3-(-7/4u-3)=0
Domain of the equation: 2u!=0
u!=0/2
u!=0
u∈R
Domain of the equation: 4u-3)!=0
u∈R
We get rid of parentheses
-5/2u+7/4u+3+1/3=0
We calculate fractions
32u^2/72u^2+(-180u)/72u^2+126u/72u^2+3=0
We multiply all the terms by the denominator
32u^2+(-180u)+126u+3*72u^2=0
We add all the numbers together, and all the variables
32u^2+126u+(-180u)+3*72u^2=0
Wy multiply elements
32u^2+216u^2+126u+(-180u)=0
We get rid of parentheses
32u^2+216u^2+126u-180u=0
We add all the numbers together, and all the variables
248u^2-54u=0
a = 248; b = -54; c = 0;
Δ = b2-4ac
Δ = -542-4·248·0
Δ = 2916
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{2916}=54$
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-54)-54}{2*248}=\frac{0}{496} =0 $
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-54)+54}{2*248}=\frac{108}{496} =27/124 $

See similar equations:

| 57=9-8w | | 62=4y+14 | | 7/4=4x;x | | b/4.8*b=b | | -9/5=-1/2u-8/3 | | -3x=x⋅-3 | | b/4.8*b=8.09*b | | 2x-9+6x-5=101 | | 8(w-9)=-8w+24 | | -0.2(7x+2)+1=9 | | x4−8=18 | | 5u-26=9(u-2) | | 5n+19=3n-7 | | 5/6u-2/3=-5/9 | | 10/x=17/15 | | 80x^2-302x-36=0 | | -11=-4+y | | 7y+8/8y-7=1/3 | | 2v-145=180 | | -6(v+1)=-8v+8 | | 9x^2-128x-320=0 | | 9x^2-138x-320=0 | | 2v-32+70+43=180 | | -8x+2x-2=-14 | | 14^(9x)-9=146 | | v-32+v+70+43=180 | | 4/x+5=6/x | | -2x+5x+38=8 | | 21/u=3 | | 3x+30+105=180 | | -2x+5x+38x=8 | | 47=r+11 |

Equations solver categories